Genome‐wide significant association between alcohol dependence and a variant in the ADH gene cluster - Frank, Josef; Mann, Karl; Kiefer, Falk; Rietschel, Marcella (Addiction biology, 2012)
Alcohol dependence (AD) is an important contributory factor to the global burden of disease. The etiology of AD involves both environmental and genetic factors, and the disorder has a heritability of around 50%. The aim of the present study was to identify susceptibility genes for AD by performing a genome‐wide association study (GWAS). The sample comprised 1333 male in‐patients with severe AD according to the Diagnostic and Statistical Manual of Mental Disorders, 4th edition, and 2168 controls. These included 487 patients and 1358 controls from a previous GWAS study by our group. All individuals were of German descent. Single‐marker tests and a polygenic score‐based analysis to assess the combined contribution of multiple markers with small effects were performed. The single nucleotide polymorphism (SNP) rs1789891, which is located between the ADH1B and ADH1C genes, achieved genome‐wide significance [P = 1.27E-8, odds ratio (OR) = 1.46]. Other markers from this region were also associated with AD, and conditional analyses indicated that these made a partially independent contribution. The SNP rs1789891 is in complete linkage disequilibrium with the functional Arg272Gln variant (P = 1.24E-7, OR = 1.31) of the ADH1C gene, which has been reported to modify the rate of ethanol oxidation to acetaldehyde in vitro. A polygenic score‐based approach produced a significant result (P = 9.66E-9). This is the first GWAS of AD to provide genome‐wide significant support for the role of the ADH gene cluster and to suggest a polygenic component to the etiology of AD. The latter result may indicate that many more AD susceptibility genes still await identification.
First published: 18 October 2011
Gesehen am 29.03.2018